MURDERING CHILDREN AS REACTION OF PSYCOPHATIC PERSONALITY DISORDER A Psychological Study of Literature in Euripides, Medea - Hadiyanto - (JURNAL LITBANG, 2004)
Literature-psychology relation ship has given much contribution to development of both disciplines of knowledge. Such relationship enables any methods within psychology to be applied to analyze literary works, and vise versa, psychological phenomenon found in literary works can give feedback to development of psychology. This essay is aimed at analyzing the cause of Medea's failure in marriage, her psychological state, and psychopathic personality disorder reaction so that Medea eventually decides to murder her own children. In this Euripides literary work, Medea, the sufferer of psychopathic personality disorder, has some psychological disorder indications such as malaclaptive behavior and personaldistress. Characteristtcs of psychopathic personality disorder are guiltless feeling and no remorse for every sadistic maladaptive behavior she has committed all her life. She has no conscience, just follows her impulsive drive without considcring other's right to live, and has no ability to change her maladaptive behavior throughout her life. Murdering her own children, king Kreon and his daughter, and dismemhering her own brother's body into pieces for the dragon ure evidence for a psychopath Medea. The importance factors huving a role to shape Metlea's personality are hiological and parentalfactor. Medea's hiologicalfoctor ts her nonreactivenerve system which leads her to commit o cruel deed oggressivellt undunable to hear somehody's advice and restriction. Wereas based on parentol factor, Medea from childhood to adulthood ,s reared in killer fomillt ancl environment, so it also shapes Medea's personality to be a cold-hlootled killer.Key words: psychopathic personality disorder, murdering, guiltless feeling,maladaptive, personal distress, biological-parental factor.